2023
DOI: 10.1186/s12954-023-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care community drug checking technologies: an insider look at the scientific principles and practical considerations

Abstract: Drug checking is increasingly being explored outside of festivals and events to be an ongoing service within communities, frequently integrated within responses to illicit drug overdose. The choice of instrumentation is a common question, and the demands on these chemical analytical instruments can be challenging as illicit substances may be more complex and include highly potent ingredients at trace levels. The answer remains nuanced as the instruments themselves are not directly comparable nor are the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…Previous research has found that less than half of a sample of regular ecstasy users who reported the use of reagent testing kits were able to describe the limitations associated with reagent testing [40]; in absence of formal drug checking services, which can provide expert advice and education concerning test results, individuals may misinterpret the information yielded by colorimetric reagent kits or administer a reagent which lacks specificity for the suspected drug class [30, 43]. With regard to those who suspected their ecstasy was adulterated with fentanyl, it should also be noted that fentanyl test strips have been shown to generate false‐positive results when MDMA samples are not sufficiently diluted [44, 45]. Given that prior work in this population that found that among the 27.8% of ecstasy users in this population whose hair tested positive for ‘bath salts’, 68.0% reported no past‐year use of such substances [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that less than half of a sample of regular ecstasy users who reported the use of reagent testing kits were able to describe the limitations associated with reagent testing [40]; in absence of formal drug checking services, which can provide expert advice and education concerning test results, individuals may misinterpret the information yielded by colorimetric reagent kits or administer a reagent which lacks specificity for the suspected drug class [30, 43]. With regard to those who suspected their ecstasy was adulterated with fentanyl, it should also be noted that fentanyl test strips have been shown to generate false‐positive results when MDMA samples are not sufficiently diluted [44, 45]. Given that prior work in this population that found that among the 27.8% of ecstasy users in this population whose hair tested positive for ‘bath salts’, 68.0% reported no past‐year use of such substances [12].…”
Section: Discussionmentioning
confidence: 99%
“…The NYC Department of Health and Mental Hygiene does list several organisations which distribute fentanyl test strips (currently, one in Bronx County, one in Brooklyn [Kings County], four in Manhattan [New York County] and two in Queens County) as well as opportunities for virtual fentanyl test strip trainings on their website [47], but these are limited to fentanyl testing. Given the described limitations associated with colorimetric reagent test kits and the current lack of drug checking services in NYC, the increasing interest in understanding ecstasy contents in this population of EDM party attendees suggests the need for formal drug checking services using additional point‐of‐care drug checking technologies [45], which can also serve to provide education and advice in the interpretation of test results.…”
Section: Discussionmentioning
confidence: 99%
“…GYDT uses a Fourier-transform infrared spectroscopy (FTIR) to test samples in combination with fentanyl and benzodiazepine immunoassay strip tests. The limitations of the service include: the FTIR has a detection limit of 5% (that is, where a substance is present at <5% of the total mass, it will not be reliably detected), the substance must be present in the FTIR library to be detected, percentage estimates where multiple substances are detected are only a general guide, inconsistent production means that the result may not be applicable to the rest of the same batch, and immunoassay tests may detect similar drug structures (analogues) rather than a specific molecule (see [27] for more information on FTIR limitations). Despite these limitations, FTIR testing conducted by trained professionals is more accurate than reagent test kits alone, and this represents an improvement on available community-level testing methods in parts of Australia not reached by CanTEST during the period under study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, fentanyl test strips may not detect other highly potent synthetic opioids, including carfentanil. 306 Similar to presumptive drug testing, these test strips may also produce false positives that may limit patient reliance on the results. Some harm reduction programs may provide more comprehensive drug checking services, including Fourier-transform infrared spectroscopy (FTIR), which can assess contaminants and verify the main component of the sample.…”
Section: Overdose Prevention and Reversalmentioning
confidence: 99%